PENGARUH VITAMIN C DAN MADU DALAM PAKAN BUATAN TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN LELE SANGKURIANG (Clarias sp) - Eliaspikel. K Yani; Felix Rebhung; Kiik Gretty Sine (Jurnal Akuatik, 2019)
This research was aimed to know the effect of vitamin C and honey addition on artificial feed on growth and life of sankuriang catfish. This study had been done from 17 th November 2016 – until12 th Jan 2017 at the faculty of marine and fisheries, department of equaculture univercity of Nusa Cendana Kupang. Sangkuriang catfish(5-7 cm, 2-5 g) where maintained in a terpaulin pond ( 0,8 m x 0,8 m x 0,8 m ) 15 individuals each for 56 days, feed on artificial feed mixed vitamin C and honey. The dose mexid vitamin C and honey were A100 mg/kg without honey, B 100 mg of vitamin + C 400 ml honey / kg of feed, C 100 mg + 800 ml honey / kg of feed and D 100 mg + 1.200 ml honey / kg of feed and the freaquence of given feed three time a day, morning, day and afternoon. This research arranged use complete random design (RAL) with four treatment and three repeat. The result of this research showed that real influence the absolute of sangkuriang catfish, where the average of growth higher the was in treatment B with dose of vitamin C 100 mg + 400 ml honey / kg of feed about 48,56. The average life sustainability of treatment B (dose of vitamin C 100 mg + 400 ml honey / kg of feed ) as much 100 % and treatment C ( dose of vitamin C 100 mg + 800 ml honey / kg of feed ) as much 100 %. The results showed the real influence. Keywords: catfish, feed, honey, treatment, maintained